Modeling the Influence of Work Environment, Discipline, and Motivation on the Performance of Vocational School Teachers in Indonesia - Ropi'i, Ahmad; Mardiyah, Siti Umi Khayatun (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to examine the effect of work environment, work discipline, and work motivation on the performance of vocational school teachers in the Office Management and Business Services program in the Special Region of Yogyakarta, Indonesia. A quantitative, explanatory research design was employed to analyze the causal relationships among variables. The research involved 100 vocational teachers selected through simple random sampling from both public and private schools. Data were collected using a validated questionnaire and analyzed using multiple regression analysis.The results indicate that all three independent variables have a significant positive impact on teacher performance. Work motivation contributed the most, with a standardized coefficient of 0.351, followed by work discipline (0.366), and work environment (0.327). Collectively, these variables explained 67.8% of the variance in teacher performance. These findings suggest that teacher effectiveness is strongly shaped by both individual psychological factors and institutional conditions. Future studies should explore additional mediating variables such as leadership style, digital readiness, or organizational commitment, and consider conducting longitudinal research across different vocational disciplines to enhance generalizability.